Wind‐Driven Bidirectional Fluttering Triboelectric Nanogenerator Via Dual Flagpole and Slot Structure Design. Issue 1 (30th July 2022) - Son, Jin‐ho; Heo, Deokjae; Goh, Dongmin; Lee, Minjoo; Chung, Jihoon; Choi, Seungtae; Lee, Sangmin
Abstract: Recently, as fossil fuel reserves have decreased and energy requirements have increased worldwide, wind energy, which has various advantages, such as ubiquitous, sustainable, clean, and infinite energy capacitance, has attracted increasing attention. In particular, wind‐driven fluttering‐type triboelectric nanogenerators (TENGs), which can utilize mechanical movement induced by wind energy based on the coupling of the triboelectric effect and electrostatic induction, have been widely studied. However, previous studies have not discussed structural device designs to harvest bidirectional wind energy. Herein, a wind‐driven bidirectional fluttering triboelectric nanogenerator (WBF‐TENG) is reported, which has a dual flagpole and slot structure design to generate electrical output against wind blowing from both directions. Considering natural wind flow in random direction, WBF‐TENG is more effective compared with the previous unidirectional fluttering TENGs. The electrical output of the WBF‐TENG is quantitatively measured and analyzed in terms of the peak and root mean square outputs depending on various design parameters and wind velocities. The findings demonstrated that the WBF‐TENG can be utilized as a swing safety light by continuously turning on 76 LEDs when riding a swing during right and left direction movements. Furthermore, the WBF‐TENG can scavenge omnidirectional wind energy by vertically stacking two devices. Abstract : A wind‐driven bidirectional fluttering triboelectric nanogenerator (WBF‐TENG), which is mechanically designed to harvest small‐scale and random flow considering natural wind, is developed. The electrical performance of the WBF‐TENG is quantitatively studied for optimized device design in terms of the root mean square (RMS) and average peak voltages according to several variables.